Hypertensive pregnancy and future maternal cardiovascular phenotype - Boardman, H (2016)
Hypertensive disorders of pregnancy are common and associated with persistent increased risk of maternal cardiovascular disease. However it is unclear which mechanisms are behind this increased risk and whether they are explained by traditional cardiovascular risk factors. I sought to characterise cardiovascular phenotypic patterns after hypertensive pregnancy and explore relevant relationships with risk factors and pregnancy characteristics. Women were identified through the John Radcliffe Hospital maternity records and recruited 5-10 years after hypertensive (cases) or normotensive pregnancy (controls). Detailed phenotyping to characterise cardiac, vascular and cerebral phenotypic differences was carried out using a range of techniques including magnetic resonance imaging, cardiac and vascular ultrasound, intravital video capillaroscopy and ambulatory monitoring. Women after hypertensive pregnancy were more likely to have adverse cardiac structure than women after normotensive pregnancy, with higher left ventricular mass and lower left ventricular volumes compared to women with a history of normotensive pregnancy. They were also more likely to have reduced aortic distensibility. Characterisation of cerebral structure demonstrated that women after preeclampsia had lower grey matter volumes and greater white matter damage compared to a control population. There were also distinct microvascular and blood pressure differences with capillary rarefaction and higher ambulatory blood pressure in women after hypertensive pregnancy compared to women after normotensive pregnancy. There were no significant differences in circulating angiogenic factors or autonomic function. Differences in left ventricular mass, cerebral white matter damage and capillary rarefaction were not explained by conventional risk factors, suggesting novel, disease-specific mechanisms may be responsible. This encompassing characterisation of postpartum maternal cardiovascular phenotype after hypertensive pregnancy highlights widespread adverse differences which are not fully explained by traditional risk factors. Understanding whether targeting these adverse phenotypic features during hypertensive pregnancy or in the early postpartum period affects clinical endpoints will be of future interest.